HUBUNGAN ANTARA EARLY LITERACY SKILLS DENGAN KEMAMPUAN SEMANTIK PADA ANAK USIA 3-5 TAHUN DI TK PUTERA BERINGIN KAB. CIREBON - Chaerunissa, Destiane Yahya; Gunawan, Gunawan (Tahta Media Group, 2024)
Background: Early literacy skills are important skills for the expansion of vocabulary and language. Through literacy activities a person can improve language skills which include the ability to understand the meaning of words, listen, speak, write, and read. Semantic ability is the ability of children to understand speech, such as the ability to understand the meaning of words spoken by the interlocutor. Objectives: This study aims to analyze and provide an overview of the relationship between early literacy skills and semantic ability in children aged 3-5 years in TK Putera Beringin Kab. Cirebon. Methods: This study is a quantitative study using a cross-sectional study design. The sampling technique used by the researcher was purposive sampling and the number of samples used was 30 respondents. The research data were analyzed using univariate and bivariate. The statistical test used in this study used the Spearman rank test. Results: In the spearman rank test results, the result of ρ value of 0.006 and r value = 0.488 which means that it shows a relationship between early literacy skills and semantic ability in children aged 3-5 years in TK Putera Beringin Kab. Cirebon with the strength of the relationship between the two variables including the medium category and the positive direction value which means that it is increasing between the value of the free variable and the bound variable. Conclusion: This research can concluded that semantic ability in children aged 3-5 years in TK Putera Beringin Kab. Cirebon is related to early literacy skills.